Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/maco.201810360
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic electrochemical impedance study of fluoride conversion coating on AZ31 magnesium alloy to improve bio‐adaptability for orthopedic application

Abstract: In the present work, fluoride conversion coating was formed on AZ31 magnesium alloy at 40 °C and the conversion time was optimized. A smooth surface with pores were formed which was observed from SEM. The crystalline MgO and MgF2 formed on the surface were confirmed by EDAX and X‐ray diffraction (XRD). The investigation on corrosion behavior of the coating was performed using potentiodynamic polarization, potentiostatic polarization and dynamic electrochemical impedance studies (DEIS). The coating stability wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 55 publications
(71 reference statements)
2
12
0
Order By: Relevance
“…In this experiment, the processed AZ31 samples were processed at 190 V constant voltage mode. Figure 2 shows the rough coral-like surface morphology of the microarc fluoride treated magnesium alloy, similar to previous MAF coatings at high voltages [15,16,30]. Figure 5…”
Section: Discussionsupporting
confidence: 75%
“…In this experiment, the processed AZ31 samples were processed at 190 V constant voltage mode. Figure 2 shows the rough coral-like surface morphology of the microarc fluoride treated magnesium alloy, similar to previous MAF coatings at high voltages [15,16,30]. Figure 5…”
Section: Discussionsupporting
confidence: 75%
“…Under chronic exposure, significant loss of dendrite and soma of neurons induced down-expressions and other behavioural deficits [ 6 , 100 ]. Fluoride Conversion Coatings (FCCs): Several authors [ [101] , [102] , [103] , [104] ] reported the development of FCCs on Mg alloys for biomedical implant applications. The coating procedure is typically performed by immersing Mg or Mg alloy substrates in 40%–48% hydrofluoric (HF) acid solution [ 69 , 105 ].…”
Section: Coatings and Their Current Statusmentioning
confidence: 99%
“…The percentage of hemolysis was calculated as, MTT assay was performed to determine the cytotoxic behavior of the SS-Ag NPs. 3-(4,5dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) was added with the cells and incubated for 4 h. 1 mL of dimethyl sulphoxide (DMSO) was added to dissolve the formazan crystals and the optical density values were measured at 570 nm using ELISA reader (Bio-Rad 680, USA) [64]. The assay was performed in triplicate and the percentage of cell viability was calculated using the following formula.…”
Section: Hemolysis Assaymentioning
confidence: 99%